PENERAPAN PROBLEM-BASED LEARNING: STUDI PADA KEMAMPUAN BERPIKIR REFLEKTIF SISWA - Fitry Wahyuni (Journal of Didactic Mathematics, 2020)
In solving the problems they face, students must think so that they can apply the right concepts to the problems they face. This process can run effectively in learning if students have good reflective thinking skills. Mathematical reflective thinking is one of the thought processes needed in the process of solving mathematical problems. The purpose of this study was to determine the increase in reflective thinking skills between students who received learning with problem-based learning and conventional learning. The research method used is quantitative research with a quasi-experimental design. The population of this study was students of grade 7 MTs Islmaiyah Medan in the academic year 2019/2020. The sample in this study was students of class 7-A and 7-B MTs Islamiyah Medan. The data were collected by giving a reflective thinking ability test instrument. The data obtained were analyzed using a two-way ANOVA statistical test. Based on the research findings, it was found that there was an increase in students' reflective thinking skills taught by problem-based learning with students taught conventionally. Where the increase in reflective thinking skills between students whose learning process using problem-based learning is significantly higher than students whose learning is through conventional learning. Based on these results, it can be concluded that in an effort to foster students' mathematical abilities, the learning model used must match the characteristics of the learning model with mathematical abilities.